AN ERROR ANALYSIS ON SENTENCE STRUCTURE IN INDONESIA'S TRANSTOOL TRANSLATION INTO ENGLISH - Endang Suciati (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2009)
Endang Suciati University of Pesantren Tinggi Darul’Ulum Jombang endangsuciati24@gmail.com Abstract Translation is defined as a process of transferring a language (source language) into another language (target language). Due regard to the text, the translation must have language compatibility between the source language and target language. However, in the process, there are sometimes some words, phrases or sentences that are not translated exactly. It means that the translations are not matched to the target language. In other words there is an error in translation. This study analyzes the structure of sentences translated from Indonesian into English through computer media namely transtool translation program. key words: transtool, error analysis Abstrak Penerjemahan diartikan sebagai suatu proses pengalihan suatu bahasa (bahasa sumber) ke bahasa lain (bahasa target). Karena berkenaan dengan teks, penerjemahan harus memiliki kesesuaian bahasa antara bahasa sumber dengan bahasa target. Namun dalam prosesnya kadang-kadang ada beberapa kata, frase atau kalimat yang tidak diterjemahkan secara tepat sesuai bahasa target. Dengan kata lain terjadi error dalam penerjemahan. Penelitian ini menganalisa struktur kalimat yang diterjemahkan dari bahasa Indonesia ke bahasa Inggris melalui media computer: Trans Tool Translation Program. kata kunci: transtool, analisis kesalahan